The scope of parliamentary immunity in the UAE Constitutional organization: Comparative Study - مصطفى, مصطفى سالم (Journal of Legal Sciences, 2021)
The immunity enjoyed by members of parliament is one of the most important guarantees for the performance of their parliamentary work, which protects them from threats or any reprisals against them.There are two types of immunity:  Objective immunity: the member does not bear any responsibility for the opinions, ideas, and statements he expresses within the council or its committees, but even outside it by some systems.  Procedural immunity: that prevents criminal actions from being taken during or outside the session of the Council, with the approval of a body specified by the constitutions of the countries under study, but it is restricted by conditions and controls stipulated. It contains constitutions, rules, and regulations for parliaments.We have discussed the scope of parliamentary immunity and the apparent problems of both types in terms of persons, subject, place, and time. In addition to its nature, characteristics, and effects. We reached several results in which we asked the constitutional legislator to make constitutional amendments to the text of Articles 81 and 82 of the UAE Constitution. And in the second party of Article 63, with its paragraphs A, B, C and Article 20 of the Iraqi Council of Representatives’ internal system. And in Article 112 of the Constitution and the internal regulations of the House of Representatives in Egypt in terms of subject matter, procedure, time, and spatial range.